2020
DOI: 10.1039/d0fo02356f
|View full text |Cite
|
Sign up to set email alerts
|

Puerarin induces mouse mesenteric vasodilation and ameliorates hypertension involving endothelial TRPV4 channels

Abstract: Puerarin derived from Pueraria induces mesenteric endothelium-dependent vasodilation involving the TRPV4-IKCa/SKCa pathway, exhibiting antihypertensive activity against high-salt-induced hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Acute 40 min puerarin treatment was found to reduce EDCs in a concentration-dependent manner and failed to inhibit the production of PGs in intact endothelial arteries, suggesting that puerarin is able to inhibit EDCs induced via Ach independently of the inhibition of TP receptor-or COX2-derived PGs. Zhou et al [94] pretreated first-order mouse mesenteric resistance arteries with intact or incomplete endothelium using 1 µM phenylephrine (Phe) to constrict them and then exposed them to cumulative doses of puerarin (0.01, 0.1, 1, 10, 20, 50, 100, and 200 µM), and they found that mesenteric arteries with intact endothelium in mice treated with puerarin relaxed and that the degree of relaxation was correlated with the dose of puerarin. Subsequently, to investigate the role of transient receptor potential vanilloid 4 (TRPV4) channels in the modulation of vasorelaxation by puerarin, mesenteric arteries of TRPV4 −/− mice were selected.…”
Section: Regulates Vasodilationmentioning
confidence: 99%
“…Acute 40 min puerarin treatment was found to reduce EDCs in a concentration-dependent manner and failed to inhibit the production of PGs in intact endothelial arteries, suggesting that puerarin is able to inhibit EDCs induced via Ach independently of the inhibition of TP receptor-or COX2-derived PGs. Zhou et al [94] pretreated first-order mouse mesenteric resistance arteries with intact or incomplete endothelium using 1 µM phenylephrine (Phe) to constrict them and then exposed them to cumulative doses of puerarin (0.01, 0.1, 1, 10, 20, 50, 100, and 200 µM), and they found that mesenteric arteries with intact endothelium in mice treated with puerarin relaxed and that the degree of relaxation was correlated with the dose of puerarin. Subsequently, to investigate the role of transient receptor potential vanilloid 4 (TRPV4) channels in the modulation of vasorelaxation by puerarin, mesenteric arteries of TRPV4 −/− mice were selected.…”
Section: Regulates Vasodilationmentioning
confidence: 99%
“…TSN binds to VDAC1. Molecular docking is widely used to assay potential bioactivity of compounds (36,37). computational modeling was performed to investigate the direct interaction between TSN and VdAc1.…”
Section: Tsn Attenuates Erastin-induced Ferroptosis and Inhibits Apop...mentioning
confidence: 99%
“…Transient receptor potential vanillin 4 (TRPV4) is a calcium permeability channel with diverse activation modes, which plays a crucial role in vascular endothelial function and vasodilation. As a TRPV4 agonist, puerarin induced endothelium-dependent vasodilation of mesenteric arteries in mice and reduced blood pressure in hypertensive mice induced by high salt, highlighting the beneficial role of puerarin in the treatment of endothelial-dysfunction-related cardiovascular diseases [ 96 ]. Puerarin also enhances vasodilation and insulin-stimulated Akt/eNOS pathways by inhibiting the NF-κB inflammatory pathway and decreasing plasma TNF-α levels [ 97 ].…”
Section: The Role Of Puerarin In Inflammatory Diseasesmentioning
confidence: 99%